Double diabetes: A distinct high‐risk group?. Issue 12 (19th August 2019) - Kietsiriroje, Noppadol; Pearson, Sam; Campbell, Matthew; Ariëns, Robert A. S.; Ajjan, Ramzi A.
Abstract: The term double diabetes (DD) has been used to refer to individuals with type 1 diabetes (T1D) who are overweight, have a family history of type 2 diabetes and/or clinical features of insulin resistance. Several pieces of evidence indicate that individuals who display features of DD are at higher risk of developing future diabetes complications, independently of average glucose control, measured as glycated haemoglobin (HbA1c) concentration. Given the increased prevalence of individuals with features of DD, pragmatic criteria are urgently required to identify and stratify this group, which will help with subsequent implementation of more effective personalized interventions. In this review, we discuss the potential criteria for the clinical identification of individuals with DD, highlighting the strengths and weaknesses of each definition. We also cover potential mechanisms of DD and how these contribute to increased risk of diabetes complications. Special emphasis is placed on the role of estimated glucose disposal rate (eGDR) in the diagnosis of DD, which can be easily incorporated into clinical practice and is predictive of adverse clinical outcome. In addition to the identification of individuals with DD, eGDR has potential utility in monitoring response to different interventions. T1D is a more heterogeneous condition than initially envisaged, and those with features of DD represent a subgroup at higher risk of complications. Pragmatic criteria for the diagnosis of individuals with DD will help with risk stratification, allowing a more personalized and targeted management strategy to improve outcome and quality of life in this population.